2020
DOI: 10.1186/s12884-020-03295-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of mean platelet volume in hypertriglyceridemia-induced acute pancreatitis during pregnancy

Abstract: Background Hypertriglyceridemia-induced acute pancreatitis during pregnancy (HTG-APP) is a rare but severe disease with high maternal-fetal mortality risk, which constitutes a systemic inflammatory process accompanied by thrombosis and bleeding disorders. However, the role of mean platelet volume (MPV) in HTG-APP remains unclear. Methods In the retrospective study, we collected 45 patients with HTG-APP as the HTG-APP group and 49 pregnant females with hypertriglyceridemia as the control group. MPV and other … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The study did not assess overall accuracy, sensitivity and specificity, so further multicenter randomized studies are needed to establish the relationship between elevated MPV and AP severity. Studies related to the development of respiratory failure and local complications have demonstrated that MPV >12 fL may serve as a risk factor for severe hypertriglyceridemic AP [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study did not assess overall accuracy, sensitivity and specificity, so further multicenter randomized studies are needed to establish the relationship between elevated MPV and AP severity. Studies related to the development of respiratory failure and local complications have demonstrated that MPV >12 fL may serve as a risk factor for severe hypertriglyceridemic AP [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rates of local complications and organ failure increase significantly and dose-dependently with the level of triglycerides ( 8 ). The trend of HTG-induced AP has been observed to increase with the gestational age and number of pregnancies ( 9 ). This disease constitutes a systemic inflammatory process accompanied by thrombosis, and bleeding disorders result in multiple organ dysfunction and disseminated intravascular coagulation ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The trend of HTG-induced AP has been observed to increase with the gestational age and number of pregnancies ( 9 ). This disease constitutes a systemic inflammatory process accompanied by thrombosis, and bleeding disorders result in multiple organ dysfunction and disseminated intravascular coagulation ( 9 ). Yang et al showed that HTG-induced AP along with a delayed diagnosis was related to a 66.7% fetal loss ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Platelet activation plays a crucial role in the occurrence and development of AP [ 80 ]. The changes in AP with different causes are inconsistent [ 81 83 ]. Multiple studies have indicated that platelets directly participate in the systemic inflammatory process of AP [ 80 , 81 ], and the key value of mean platelet volume (MPV) in determining the severity of AP when combined with other inflammatory markers and scoring systems has been discovered [ 81 ].…”
Section: Choice Of Blood Purification Modalitymentioning
confidence: 99%